Avaliação bromatológica e pós-colheita de frutos de goiaba - Pereira, Sara Maria Andrade (2018)
Brazil is currently considered the world's third largest fruit producer and one of the largest guava producers in the world. Guava (Psidium guajava L.) is a fruit considered as one of the best sources of vitamin C and presents great social and economic im